A method for comparing wave energy converter conceptual designs based on potential power capture. (January 2018) - Bubbar, K.; Buckham, B.; Wild, P.
Abstract: The design space for ocean wave energy converters is notable for its divergence. To facilitate convergence, and thereby support commercialization, we present a new simple method for analysis and comparison of alternative device architectures at an early stage of the design process. Using Thévenin's theorem, Falnes crafted an ingenious solution for the monochromatic optimal power capture of heaving point absorber devices by forming a mechanical impedance matching problem between the device and the power take-off. However, his solutions are limited by device architecture complexity. In this paper, we use the mechanical circuit framework to extend Falnes' method to form and solve the impedance matching problem and calculate the optimal power capture for converter architectures of arbitrary complexity. The new technique is first applied to reprove Falnes' findings and then to assess a complex converter architecture, proposed by Korde. This work also provides insight into a master-slave relationship between the geometry and power take-off force control problems that are inherent to converter design, and it reveals a hierarchy of distinct design objectives unbeknownst to Korde for his device. Finally, we show how application of the master-slave principle leads to the reduction in the dimensionality of the associated design space. Highlights: Introduced mechanical circuits to solve impedance matching problem for infinitely complex WECs. Reproved Falnes' optimal PTO force equations for SRPAs using mechanical circuits. Introduced master-slave relationship between the geometric and PTO force parameters. Introduced the WEC canonical form as phenomenological equivalent architecture. Applied mechanical circuits to Korde's WEC architecture and developed new insights.